In Someone Else’s Shoes : Promoting Prosocial Behavior Through Perspective Taking - Rodríguez Chatruc, Marisol; Rozo, Sandra V. (World Bank, Washington, DC, 2021)
Can taking the perspective of an out-group reduce prejudice and promote prosociality Building on insights from social psychology, this paper studies the case of Colombian natives and Venezuelan immigrants. This was done by conducting an online experiment in which natives were randomly assigned either to play an online game that immersed them in the life of a Venezuelan migrant or to watch a documentary about Venezuelans crossing the border on foot. Relative to a control group, both treatments increased altruism towards Venezuelans and improved some attitudes, but only the game significantly increased self-reported trust.